2017
DOI: 10.1007/978-3-319-65831-5_12
|View full text |Cite
|
Sign up to set email alerts
|

Software Architecture Risk Containers

Abstract: Abstract. Our motivation is to determine whether risks such as implementation error-proneness can be isolated into three types of containers at design time. This paper identifies several container candidates in other research that fit the risk container concept. Two industrial case studies were used to determine which of three container types tested is most effective at isolating and predicting at design time the risk of implementation error-proneness. We found that Design Rule Containers were more effective t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(32 citation statements)
references
References 10 publications
1
31
0
Order By: Relevance
“…The work in [1] [2] describes DR Containers derived from the Design Rule Spaces (DRSpaces) proposed by Xiao et al [3]. DRSpaces are graphs based on design rules (key interfaces) that split an architecture into independent modules.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…The work in [1] [2] describes DR Containers derived from the Design Rule Spaces (DRSpaces) proposed by Xiao et al [3]. DRSpaces are graphs based on design rules (key interfaces) that split an architecture into independent modules.…”
Section: Related Workmentioning
confidence: 99%
“…To improve chances of project success, practitioners must be able to work with the risk container to manage the isolated risks. We concluded that more work is necessary to determine whether different types of risk containers are meaningful to practitioners [1].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations